Analisis Pragmatik Terjemahan Film Mean Girls (2004) : Telaah Tindak Tutur, Implikatur, dan Kesantunan - Andina Hadawiyah; Friscila Sinaga; Khairun Nisa; Roy Pandapotan Panjaitan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the pragmatic aspects in the subtitle translation of Mean Girls (2004) from English to Indonesian, focusing on speech acts, implicatures, and politeness strategies. Using a descriptive qualitative approach, data were collected through observation and recording of film dialogues, then analyzed based on pragmatic theory. The results show that the functions and intentions of speech acts are generally maintained in the translation, although there is a softening of intensity or nuance to fit the norms of Indonesian politeness. In terms of implicature, there is a shift or loss of implied meaning, especially in expressions of humor, irony, and cultural idioms that are difficult to translate directly. Politeness strategies in the original version that tend to be frontal and explicit are often mitigated in translation to conform to Indonesian communication norms that prioritize social harmony. The findings emphasize the importance of cultural sensitivity and pragmatic context understanding in audiovisual translation to effectively convey the meaning and nuances of intercultural communication.